Mechanical properties of soil reinforced with polypropylene fibre. Issue 2 (10th April 2019) - Hojjati, Fatemeh; Sarkar, Alireza
Abstract : Fibre-reinforced soil is defined as a method for soil stabilisation, which is superior to other stabilisation methods by cement and lime additives. In this study, various static and dynamic triaxial tests for fine-grained soil reinforced with synthetic fibres made of polypropylene were conducted under different confining pressures. Experimental results indicate that the effect of fibres on improving the strength characteristics of the soil in cyclic loading is much more than for static loading. An assessment of dynamic behaviour of fibre-reinforced soil under cyclic loading based on a regression model for determining the resilient modulus revealed that increasing the vertical deviator stress and confining pressure at the same time increased the resilient modulus of fibre-reinforced soil. In addition, for a vertical deviator stress of 200 kPa, it increases 40% more than the resilient modulus of unreinforced soil specimens. An 80% increase in the resilient modulus of fibre-reinforced soil from cyclic triaxial tests compared with a 13% increase in the unconfined static tests was also found, indicating the effective application of fibres in the dynamic loading conditions of soil. In other words, stabilising the soil using fibres is recommended for dynamic loadings, for instance in pavements.